Society of Vacuum Coaters 49th Annual Technical Conference proceedings, April 22-27, 2006, Washington, D.C. (Society of Vacuum Coaters, 2006)
The Society of Vacuum Coaters is a non-profit professional and educational organization, dedicated to the development of equipment and processes for high-volume production of coatings using vacuum-based processes.
Keywords: Vapor-plating -- Congresses.; elektronické knihy; electronic books